PENERAPAN MANAJEMEN SEKURITI DENGAN STANDAR, KOMPONEN, DAN K3 DI PT. PERTAMINA HULU ROKAN - Annisa Erniyanti; Edy Soesanto, Kania Annisa Putri, Febriyani Dwi Rahma (Jurnal Ekonomi dan Bisnis, 2024)
This research discusses the implementation of Standards, Components and K3 at PT. Pertamina Hulu Rokan. Use of the Occupational Health and Safety (K3) System as an effort to protect workers from danger or potential negative impacts of work accidents. One of the reasons for conducting this research to increase employee productivity is occupational health and safety (K3), which is also a human right. A combination with security management in stages can be carried out to implement security and loss prevention efforts as an effort to reduce the risk of work accidents. The research location is PT Pertamina Hulu Rokan. The method applied in this research is the Literature Study Approach. The result is that there are 4 important aspects in implementing K3, namely the need to identify hazards in the work environment, provide training and competency for employees, employee communication and participation, and the availability of adequate health facilities. Another aspect is through the concept of security management including work security planning and security standards based on security management.